Challenges in design and development of high entropy alloys: A thermodynamic and kinetic perspective. (November 2020) - Guruvidyathri, K.; Vaidya, M.; Murty, B.S.
Abstract: High entropy alloys (HEAs) have brought a renewed interest to thermodynamics and kinetics. Proper understanding and treatment of relevant quantities are important for the effective theoretical design framework. Since the ideal mixing treatment is useful, its validity is evaluated through checking the Lupis and Elliot effect on extensive binary data and temperature dependency effect on limited HEA data. The physical basis of different configurational entropy contributions and mismatch entropy are elucidated. New alloy possibilities such as immiscible HEAs are revealed. Influence of elemental atmospheres and crystalline nature of matrices on diffusion in HEAs are discussed. Graphical abstract: Image, graphical abstract